The Effect of Green Marketing on Purchase Decision with Brand Image as A Mediating Variable: A Case Study at Satvika Bhoga Denpasar - I Made Denny Wahyu Aditya; I Gst. A. Kt. Gd. Suasana (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to analyze the effect of green marketing on purchase decision with brand image as a mediating variable among consumers of Satvika Bhoga in Denpasar. The research is grounded in the increasing consumer awareness of environmental issues, which has not yet been fully reflected in consistent purchasing behavior toward environmentally friendly products. Despite a rise in environmental consciousness, many consumers remain skeptical or indifferent unless a brand manages to build a credible and positive image aligned with eco-friendly values. Employing a quantitative approach with an associative research design, data were collected through structured questionnaires distributed to Satvika Bhoga consumers, selected using purposive sampling. The analysis was conducted using path analysis and the Sobel test to assess both direct and indirect relationships among variables. These methods allowed the researchers to examine not only the magnitude of influence but also the mediating role of brand image in shaping purchase decisions. The results indicate that green marketing has a positive and significant effect on purchase decision and significantly strengthens Satvika Bhoga’s brand image as an environmentally conscious brand. Furthermore, brand image was found to have a strong and statistically significant influence on purchase decision, confirming its role as a partial mediator. This implies that green marketing efforts, such as eco-friendly packaging, sustainable sourcing, and environmental messaging, not only influence consumer decisions directly but also enhance the overall brand perception, which in turn further motivates consumers to make purchases. Thus, businesses aiming to improve eco-product sales should prioritize consistent green marketing strategies that reinforce a trustworthy and environmentally responsible brand image.